Strength of the individual glasses of curved, annealed and laminated glass used in automotive windscreens. (May 2021) - Müller-Braun, Steffen; Brokmann, Christopher; Schneider, Jens; Kolling, Stefan
Highlights: Destructive strength tests for curved glass. Strength of the inner glass surfaces of laminated glass. Quantitative strength distributions for different windscreen areas. Strength differ significantly for different windscreen areas. Abstract: Failure of glass is based on microdefects at the glass surface. These can vary in their geometry and quantity whereby they are influenced by a large number of parameters from production and use. For a safe design and precise failure prediction, the distribution of these microdefects over the considered glass surface must be known. Particularly for windscreens, this is of interest with regard to pedestrian safety in case of head impact. In this paper, extensive investigations are presented concerning the different strengths and thus the distribution of microdefects on the different areas of the windscreen. Windscreens are laminated glass panes consisting of two individual panes and a polymer interlayer. It is shown that the different glass surfaces of this windscreen differ from each other with regard to their strength distributions. Significant differences can be seen due to the enamel area and the glass surfaces facing the interlayer. For the investigations, a method was developed that allows both to take into account the curved geometry of the windscreen and to destructively test the glass surface facing the interlayer by separating the laminate. In addition to investigations on laminated windscreens, single glass panes were examined in order to identify influences from production and lamination. The results of the destructive strength tests are statistically evaluated. It can be observed that the glass surfaces facing the interlayer show very high strengths, while the enamel areas show low strengths independent of the interlayer. It can also be seen that the concave surfaces have slightly higher strengths than the convex surfaces. However, higher strengths are also associated with higher scattering.